The Effect of Inquiry Learning Model with STEM Approach on Students' Critical Thinking Skills in Science Learning - Wicaksono, Iwan; Firdausy, Julia Esa Ayu; Sutarto, Sutarto; Indrawati, Indrawati; Ridlo, Zainur Rasyid (Universitas Lambung Mangkurat, 2024)
Critical thinking is a skill needed to solve problems in the 21st century. However, the critical thinking skills of Indonesian students are still considered low, as confirmed by PISA research results. This low critical thinking ability is due to students' limited understanding of factual and conceptual information when solving problems. One learning model that can serve as an alternative to improving students' critical thinking skills is the Inquiry model with a STEM approach. In this model, students are actively engaged in learning, as the process focuses on them. Additionally, the STEM approach enhances students' critical thinking abilities because it integrates various fields of knowledge, enabling students to think from multiple perspectives and become accustomed to critical thinking. The purpose of this research was to determine the effect of the Inquiry learning model with a STEM approach on students' critical thinking skills. This quantitative research was conducted at Mts 1 Jember during the even semester of the 2024/2025 academic year. The sample included class VIII B as the experimental group and class VIII D as the control group, selected through purposive sampling. Data collection techniques involved tests as the primary instrument, with supporting instruments such as observation, interviews, and documentation. Data analysis was conducted using the Independent Sample t-test, which showed a significance value (2-tailed) of 0.000 < 0.05. The results indicated a moderate increase in students' critical thinking skills, with a score of 0.68. From this analysis, it can be concluded that the use of the Inquiry learning model with a STEM approach has a significant positive impact on improving students' critical thinking skills.